Coherent integration and detection algorithm for hypersonic target based on modified pulse compression and Keystone transform. Issue 25 (28th September 2021) - Yu, Wenchao; Lu, Xingyu; Su, Weimin; Gu, Hong; Yang, Jianchao
Abstract: This letter considers the coherent integration and detection for hypersonic target in the first‐order approximate (FOA) echo model. The proposed algorithm first accomplishes the modified pulse compression utilising the designed reference signal, then conducts the Keystone transform (KT) based coherent integration method to detect the target. Compared with the existing methods which model the received signal without considering the target's intrapulse motion, the proposed method has a lower modeling error and can maintain good noise robustness for weak hypersonic target detection. Experimental results are given to show the effectiveness of the proposed method.